Dạy học đọc hiểu văn bản kí cho học sinh lớp 6 theo định hướng phát triển năng lực - Nguyễn, Thu Hường; Lê, Lan Hương (Tạp chí Giáo dục, 2024)
Chronicle is one of the genres that plays an important role in Vietnamese literature but is also a genre that does not easily create interest for students. With the unique characteristics of this genre, teachers need to have a method of teaching reading comprehension so that students can read and understand the content of the text actively and creatively. Based on the study of concepts and characteristics of chronicle genre and principles when teaching this genres, the article proposes to organize activities of teaching reading comprehension of chronicle genre according to a three-stage model: before reading, while reading and after reading to form and develop competence for middle school students. The research results of the article contribute to solving the difficulties and confusion of teachers and students in the first years of implementing the new curriculum and textbooks.